Comparative Study of the Use of Learning Modules and Learning Motivation on Integrated Science Learning Outcomes of Junior High School Students in Jember - Robith Firdausi Ahmad (Journal of Education Technology and Inovation, 2024)
The teacher as the main actor in learning is required to be able to provide meaning and understanding of each chapter studied. Teachers must be able to develop Integrated Science lessons in such a way that they can be challenging, impressive and excite students in learning. From this view, it can be concluded that to improve the cognitive and mental development of students optimally, the process of interaction and communication. The existence of an effective and good module must meet various existing criteria such as communicative, detailed, simple and straightforward, attractive layout, pictures, tables, graphs and other illustrations, concise and practical examples. Through the learning module media, integrated science material will be better presented and effectively support student learning success. This research uses a comparative quantitative approach. The sample in the study were seventh grade students with a total of 62 students in the jember district analysed using the independent T test. the conclusion of the study which states that there is no more dominant difference between the use of learning modules and learning motivation on student learning outcomes of integrated science subjects of class VIII junior high school students in jember